2019
DOI: 10.1111/jfb.14110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on sperm motility of burbot Lota lota: spontaneous activation and calcium dependency

Abstract: Several factors regulating activation of spermatozoon motility in Eurasian burbot, Lota lota, including osmolality, calcium (Ca2+) ions, and temperature were investigated. Spermatozoon motility in Eurasian burbot, Lota lota was assessed at 4 and 30°C in seminal fluid, isotonic media (with and without Ca2+) and hypotonic media (with and without Ca2+). Spermatozoa were spontaneously activated in seminal fluid at 20°C and the maximum motility was recorded at 30°C, which is out of the spawning temperature range, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
(66 reference statements)
0
10
0
1
Order By: Relevance
“…Several studies have been conducted to mitigate the population decline directly or indirectly. Most of them have focused on understanding its life cycle, enhancing reproduction in hatcheries, or understanding and improving sperm physiology [ 3 , 16 , 20 , 21 , 22 , 23 , 24 ]. Nevertheless, sperm energy budgeting (production, accumulation, and usage) and its adaptation to raised temperatures were still unexplored before this study commenced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been conducted to mitigate the population decline directly or indirectly. Most of them have focused on understanding its life cycle, enhancing reproduction in hatcheries, or understanding and improving sperm physiology [ 3 , 16 , 20 , 21 , 22 , 23 , 24 ]. Nevertheless, sperm energy budgeting (production, accumulation, and usage) and its adaptation to raised temperatures were still unexplored before this study commenced.…”
Section: Discussionmentioning
confidence: 99%
“…A dominant energy contribution of any of the energetic pathways during the motile state was determined by analyzing motility parameters in AM without (control) and with each inhibitor (DOG, NaF, and NaN 3 ) and the uncoupler (CCCP). For this, a 40 µL drop of AM (with or without reagents) containing 0.25% pluronic acid was placed onto a microscope slide, and sperm were added using the tip of an insulin syringe needle and thoroughly mixed to a dilution of ~1:10,000 [ 16 ] to obtain the appropriate concentration for analysis. All motility records were taken at 4 ± 1 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies of burbot have reported specific and unique properties of spermatozoa. Findings regarding triggering of spontaneous spermatozoon activation in seminal fluid by increased temperature have been contradictory, including no activation with temperature rise from 2 to 10 • C (Zuccarelli et al, 2007), spontaneous activation at temperatures >5 • C (Lahnsteiner et al, 1997), and spontaneous activation at 20 • C with maximum motility rate at 30 • C (Dadras et al, 2019). These reports show that burbot spermatozoon motility can be activated by increasing temperature, a unique trait among fishes.…”
Section: Introductionmentioning
confidence: 95%
“…For evaluation of spermatozoon motility and cell volume changes, solutions with osmolality in range of 11-280 mOsm kg −1 were prepared including seminal fluid (SF) according to Dadras et al (2019), pH 8.1, 280 mOsm kg −1 ; 10 mM Tris-HCl buffer, pH 8.5, 125 mM NaCl, 2 mM KCl, and 1 mM Ca 2+ , 297 mOsm kg −1 as ionic isotonic medium (AM); 10 mM Tris-HCl buffer, pH 8.5, 270 mM sucrose, 263 mOsm kg −1 as non-ionic isotonic medium (Suc 270); 10 mM Tris-HCl buffer, pH 8.5, 270 mM sucrose, and 1 mM CaCl 2 , 263 mOsm kg −1 as non-ionic isotonic medium (Suc 270 + Ca 2+ ); 10 mM Tris-HCl buffer, pH 8.5,11 mOsm kg −1 as ionic hypotonic medium (Tris); 10 mM Tris-HCl buffer and 1 mM CaCl 2 , pH 8.5, 11 mOsm kg −1 as ionic hypotonic medium (Tris + Ca 2+ ); 10 mM Tris-HCl buffer, pH 8.5, and 100 mM sucrose, 128 mOsm kg −1 as non-ionic hypotonic medium (Suc 100); 10 mM Tris-HCl buffer, pH 8.5, 100 mM sucrose, and 1 mM CaCl 2 , 128 mOsm kg −1 as non-ionic hypotonic medium (Suc 100 + Ca 2 ).…”
Section: Media and Temperature Used For Spermatozoon Motility And Cell Volume Assessmentmentioning
confidence: 99%
See 1 more Smart Citation